2019
DOI: 10.1093/pm/pnz143
|View full text |Cite
|
Sign up to set email alerts
|

Injectable Amniotic Membrane/Umbilical Cord Particulate for Knee Osteoarthritis: A Prospective, Single-Center Pilot Study

Abstract: ObjectiveTo evaluate the short-term safety and effectiveness of amniotic membrane/umbilical cord particulate (AMUC) in managing pain in patients with various severities of knee osteoarthritis (OA).DesignSingle-center, prospective, investigator-initiated pilot study.SettingPrivate practice.SubjectsA total of 20 knee OA patients aged ≥18 years were enrolled with pain >40 mm, as determined by the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC)–A.MethodsPatients received an ultrasound-guided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 55 publications
2
42
0
Order By: Relevance
“…[ 21 ] Pre-clinical and clinical studies have confirmed these therapeutic benefits in diseased joints where particulate AMUC attenuated progressive cartilage degeneration and provided pain relief of symptomatic knee OA. [ 12 , 13 ] Considering that the knee and facet share similar anatomical features and osteoarthritic changes have been a universal finding in facet degeneration, [ 4 ] it is not surprising the current case series show similar therapeutic effects as previously seen in those studies.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…[ 21 ] Pre-clinical and clinical studies have confirmed these therapeutic benefits in diseased joints where particulate AMUC attenuated progressive cartilage degeneration and provided pain relief of symptomatic knee OA. [ 12 , 13 ] Considering that the knee and facet share similar anatomical features and osteoarthritic changes have been a universal finding in facet degeneration, [ 4 ] it is not surprising the current case series show similar therapeutic effects as previously seen in those studies.…”
Section: Discussionsupporting
confidence: 70%
“…This dose was recently shown to attenuate pain in knee OA. [ 13 ] A total of 0.4 mL was injected into the zygapophysial intra-articular space while 0.1 mL was injected around the inferior capsule area. Patients were allowed to return immediately to normal activities.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subjects who received ASA injections demonstrated superior efficacy in measures of pain and function at 3 and 6 months post-treatment 43 . In a separate study, a noted reduction in pain at 6 months post-injection was reported for 20 OA patients that were treated with an IA injection of morselized amniotic membrane/umbilical cord tissue 44 . Importantly, no serious, unanticipated, product-related adverse Several commercial formulations containing placental tissue particulates have been marketed as HCT/P's regulated by the FDA under section 361 of the PHS act and 21 CRF part 1,271.…”
Section: Discussionmentioning
confidence: 89%
“…A recent prospective pilot study further demonstrated that one or two injections of 50 mg AM/UC particulate significantly improved pain and physical function in mild knee OA for up to 6 months. 20 Given these encouraging findings, we conducted a retrospective study to assess the clinical benefit of a single intra-articular injection of 100 mg AM/UC particulate in alleviating pain and promoting functional recovery in patients with moderate-to-severe knee OA.…”
Section: Introductionmentioning
confidence: 99%